Sosialisasi Inklusif untuk Pengembangan Bakat dan Kreativitas Anak di Lembaga Paud - Nurul Aini MM. Sodik; Siti Nur Azkiah I. Hulawa; Salsa Aprillia Patilima; Alia Azizah Sapii; Esperansa Mile (Lembaga Pengembangan Kinerja Dosen, 2025)
Play for early childhood is very important in the development of his personality. Playing for a child is not just filling time, but a medium for children to learn. Every form of play activity in children has a positive value for the development of their personality. However, free play is often the key to unlocking the creative talents that every human being possesses. Playing with children is useful for exploring their world, developing their competence to cope with it, and fostering their creativity. The function of play for early childhood can be used as an intervention that, if implemented properly, whether equipped with tools or without tools, will greatly assist social, emotional, cognitive, affective, and psychomotor development in general, and develop children's creativity.